ANTIBACTERIAL ACTIVITY PROFILE OF MANGROVE ENDOPHYTIC FUNGI ISOLATED FROM BERAU REGENCY, INDONESIA - Ferdina Tri Laksmita; . Sukarno; Slamet Budjianto; Siti Irma Rahmawati; Rikno Harmoko; Fauzia Nurul Izzati; Saiful Bachri; . Anidah; Salcia Inka Nelanda; Armaiki Yusmur; . Aslan; Muhammad Ilman (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
Mangrove endophytic fungi have the potential to produce secondary metabolites with antibacterial properties. This study aimed to obtain endophytic mold isolates associated with mangrove plants and their antimicrobial activity. Seventeen endophytic molds were isolated from 7 mangrove species originating from Berau, East Kalimantan, Indonesia. Three extracts from the mold isolates OJ-B, OJ-Bu, and 6Xg-Bh showed the highest antibacterial activity with an inhibition zone of 9.63–25.4 mm and with MIC (minimum inhibitory concentration) and MBC (minimum bactericidal concentration) values ??of around 0.625–5 and 2.5–10 mg mL–1, respectively. LC-MS (liquid chromatography-mass spectrometry) analysis identified several compounds with antibacterial potential, namely beauvericin, choline, nicotinic acid, pyridoxine, quinoline, cyclo (phenylalanyl-prolyl), fusarin c, oleamide and borrelidin. The 3 species were molecularly identified as Diaporthe phaseolorum, Fusarium proliferatum and Phomopsis sp. Thus, the endophytic molds from several of the mangrove species produced bioactive compounds as antibacterial. Kapang endofit mangrove berpotensi menghasilkan metabolit sekunder yang bersifat antibakteri. Penelitian ini bertujuan mendapatkan isolat kapang endofit yang berasosiasi dengan tanaman mangrove beserta aktivitas antimikrobanya. Tujuh belas kapang endofit diisolasi dari 7 spesies mangrove asal Berau, Kalimantan Timur, Indonesia. Tiga ekstrak dari isolat kapang OJ-B, OJ-Bu, dan 6Xg-Bh memiliki aktivitas antibakteri tertinggi dengan zona hambat 9.63–25.4 mm dan dengan nilai MIC dan MBC masing-masing sekitar 0.625-5 dan 2.5–10 mg mL–1. Analisis LC-MS menunjukkan beberapa senyawa dengan potensi antibakteri yaitu beauvericin, choline, nicotinic acid, pyridoxine, quinoline, cyclo (phenylalanyl-prolyl), fusarin c, oleamide dan borrelidin. Uji molekuler menunjukkan 3 spesies terindentifikasi sebagai Diaporthe phaseolorum, Fusarium proliferatum dan Phomopsis sp. Hasil menunjukkan kapang endofit dari beberapa spesies mangrove tersebut mampu menghasilkan senyawa bioaktif sebagai antibakteri.